1998
DOI: 10.1287/opre.46.4.463
|View full text |Cite
|
Sign up to set email alerts
|

A Primal Method for the Solution of the Groundwater Quality Management Problem

Abstract: A new algorithm for the solution of the groundwater quality management problem is presented. The method assumes that most of the computational effort in such problems involves evaluation of the concentrations and their derivatives with respect to the pumping rates at the control points. The methodology proposed herein is a combination of the cutting plane method and the primal method. In this approach each line search moves from a feasible point towards the solution of a subproblem with linear constraints and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…For example, a combined cutting-plane and primal method (Tucciarelli et al 1998) demonstrated better convergence properties than an implementation using a reduced gradient method (Murtagh and Saunders 1987) when solving a groundwater quality management formulation. The iterative steps of the combined cutting-plane and primal method result in similar behavior to that described above for active set gradient-projection methods.…”
Section: The Interior-point Boundary Projection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a combined cutting-plane and primal method (Tucciarelli et al 1998) demonstrated better convergence properties than an implementation using a reduced gradient method (Murtagh and Saunders 1987) when solving a groundwater quality management formulation. The iterative steps of the combined cutting-plane and primal method result in similar behavior to that described above for active set gradient-projection methods.…”
Section: The Interior-point Boundary Projection Methodsmentioning
confidence: 99%
“…The example is the same problem presented by Tucciarelli et al (1998), which is shown in Figure 4 and is stated as x max 2 and the initial value for w = 1 0. Additionally, set the termination criterion on w to 0.01; that is, when the value of w falls below this criterion the algorithm stops and the current solution is returned.…”
Section: Application Of the Ipbp To A Numerical Examplementioning
confidence: 99%